Supportive Care Network: Evaluation of Its Impact on the Performance of a Urology Department - Hugo Antunes; Edgar Tavares-da-Silva; Miguel Eliseu; Belmiro Parada; Maria Cunha; António Roseiro; Arnaldo Figueiredo (Acta Médica Portuguesa, 2018)
Introduction: Hospitals are dealing with patients who may have clinical discharge but cannot return to their home due to non-medical issues. Material and Methods: Cross-sectional analysis of all the cases referred to the Integrated Care Network during the year 2016. Evaluation of waiting times, typology, reason for referral and clinical parameters. IBM SPSS 24.0 software was used for all statistical analyses. Results: In the evaluated period, 2294 patients were discharged from our department. Of these, 55 were referred to Integrated Care Network. The mean length of hospitalization of the patients referred to the network was 20.6 ± 11.4 days, and the mean overall length of hospital stay in the period analyzed was 4.8 ± 0.9 days. The mean time between hospitalization and referral for continuing care was 10.7 ± 7.2 days. The time between referral and discharge of the hospital was 10.0 ± 8.7 days. Thirty-nine (70.9%) patients were hospitalized for oncological diseases. The most common referral was to Palliative Care units (n = 16; 29.1%). Patients referred to Palliative Care units showed the largest waiting times between the referral for the network and the hospital discharge, 12.2 ± 10.51 days. We observed 289 hospitalization days with patients who had no need of specialized urological care. Discussion: In order to reduce time between referral to the network and hospital discharge, there is a need for enhanced cooperation and coordination among doctors, nurses and social workers. Conclusion: Early identification by physicians and nurses of patients who will require care after discharge will provide a better response from social workers and increased hospital performance.